Diseño de un fotobiorreactor para la producción de biomasa a partir de la luz solar (2017)
The present work presents the results of the design of a photobioreactor for an open field for the whole year 2016, taking into account the solar light as the main parameter, starting from the selection of the type of photobioreactor and the location of the same in a city of Colombia. Based on data taken from the IDEAM (Institute of Hydrology, Meteorology and Environmental Studies), the incident light was characterized at the location of the photobioreactor. From this information, the amounts of energy incident on the photobioreactor were defined and calculated, the transmitted irradiance, and the amount of light that reached the culture of microalgae actually, that is, the average irradiance. From the amount of energy reached by the culture, the specific growth rate at which the microalgae were to be grown was determined, considering the average irradiance, a maximum specific growth rate and a photoinhibition constant, where the latter two values were taken from the literature. The biomass productivity obtained for all 2016 was 0.88g / h * m3, which is 5% lower than those achieved in three countries (the Netherlands, France and Algeria), where on average they achieved a productivity of 0,93 g / h*m3; with which it can be concluded that to implement this type of systems for the culture of microalgae in a country that does not present stations, is a great tool to reduce the consumption of the fossil fuels and to contribute in this way to the environment.